The effects of external factor, work-related factor and personal factor towards the turnover behavior among private sector employees in Muar district / Siti Nur Izzaty Norizan - Norizan, Siti Nur Izzaty (Faculty of Business and Management, 2018)
This paper is focusing on the effects of external factor, work-related factor and personal factor on the employee turnover among the employees in private company in Muar district. The researcher was conducted this research in Muar district and involved of 162 respondents who worked in several private company in Muar district. The respondents have answered the questionnaires that have been distributed to them in order to get the finding for further analysis. The researcher used convenience sampling in this research and used SPSS program in interpreting the data from the questionnaires. The results are in terms of the demographic profile of the respondents, descriptive analysis, reliability analysis, and regression analysis in order to answer the research questions and research objectives. The results of this research are supposed to help the management in the company to handle with employee turnover problem.